Similarities In Uzbek and Arab Families: Values, Customs, and Social-Psychological Aspects - Sayfutdinovna, Arzumetova Zarifa (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
In an era of intensifying globalization, the preservation of cultural heritage and traditional family values has become increasingly vital. The family, as a fundamental social institution, reflects distinct cultural identities through its structure, values, and interpersonal dynamics. The historical and cultural ties between Uzbekistan and Arab nations provide a unique opportunity to investigate similarities in familial traditions. Prior works by scholars such as Al-Jahiz and Ibn Khaldun underscore long-standing parallels in social norms between these peoples. While existing studies highlight isolated features of either Uzbek or Arab family systems, comparative cross-cultural research systematically analyzing their shared structural and psychosocial traits remains limited. This study aims to explore the structural, value-based, and socio-psychological commonalities in Uzbek and Arab families, with a focus on respect for elders, collective decision-making, and the influence of traditional ceremonies. Findings reveal that both cultures predominantly follow extended family models characterized by patriarchal structures, multi-generational living, and high regard for familial unity. Core values such as reverence for parents, kinship, adherence to traditions, and collectivism were rated similarly high in both cultures. By applying cross-cultural psychology frameworks such as Schwartz’s value theory and Bronfenbrenner’s ecological model this research offers a comprehensive comparative perspective on family systems across two culturally rich societies. The study contributes to broader discussions on cultural identity and intercultural communication, offering insights for fostering mutual understanding in multicultural contexts and guiding efforts to preserve traditional family values amid global cultural convergence.